Plasma tumour necrosis factor alpha in cystic fibrosis. Issue 2 (February 1991) - Norman, D; Elborn, J S; Cordon, S M; Rayner, R J; Wiseman, M S; Hiller, E J; Shale, D J
Abstract : Plasma tumour necrosis factor alpha (alpha) concentration is increased in acute Gram negative sepsis, but the effect of chronic infection on plasma concentrations is unknown. A study was carried out in patients with cystic fibrosis to determine the effect of chronic lung infection with Pseudomonas aeruginosa on the plasma concentration of tumour necrosis factor and two other indicators of the inflammatory response, circulating C reactive protein and neutrophil elastase-alpha 1 antiproteinase complex (elastase complex). The concentration of immunoreactive tumour necrosis factor in plasma was greater than the upper 95% confidence interval for healthy subjects (2.6 U/ml) on 129 out of 189 occasions in 14 patients observed for about a year. The increase in tumour necrosis factor was associated with increased circulating C reactive protein and elastase complex. Twelve patients with an exacerbation of respiratory symptoms were studied before and after two weeks' treatment with anti-pseudomonal antibiotics. All three indicators of the inflammatory response fell after treatment, though median tumour necrosis factor (4.8 U/ml) and elastase complex (0.41 microgram/ml) concentrations remained above the upper limits for healthy subjects. During a period of clinical stability plasma tumour necrosis factor was increased in 10 of the 12 patients, elastase complex was increased in 10 of the 12, and C reactive protein was increased in seven. Increased plasma immunoreactive tumour necrosis factor was a feature of the near continuous inflammatory response to chronic P aeruginosa infection in cystic fibrosis and may be a factor contributing to the progressive lung destruction seen in this disease.